The anti-trickster at play: Representing First Nations artists and art in the art galleries and museums of northern British Columbia. - Schroeter, Annette Catherine (Author); Mills, Antonia (Thesis advisor); Harris, Heather (Thesis advisor); University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2008)
First Nations artists in Canada are currently engaged in a struggle to challenge a colonialist system which has largely ignored, rejected and minimized their contributions to the mainstream Canadian art discourse and society. The attempt to engage in this discourse is not the only issue here, but also a peoples' attempt to communicate inconsistencies and weaknesses in contemporary Canadian society that continue to erode the movement toward a just and equal reality. A central area of turmoil is the public art galleries and museums as they have recently begun to deconstruct and redefine themselves since many of them have been challenged to address a colonialist system of oppression and destruction which they have contributed to and maintained. These are significant and pervasive sites in Canadian society with social, political and economic responsibilities to the communities in which they are situated. As a result, some of these art galleries and museums, through their work of programming and collecting, have actively engaged with the First Nation's struggle to revitalize and strengthen their cultural autonomy.--P.ii. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1435048